Power through: A new concept in the empowerment discourse - Galiè, Alessandra; Farnworth, Cathy Rozel (International Livestock Research Institute, 2019)
Presented by Alessandra Galie (ILRI) and Cathy Farnworth (independent) on 27 November 2019, as part of the webinar 'Power through: A new concept in the empowerment discourse'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the International Livestock Research Institute (ILRI).